The Unfolding Gospel : How the Good News Makes Sense of Discipleship, Church, Mission, and Everything Else. - Bowen, John P. (Book collections on Project MUSE., 2021)
"Many congregations and their leaders are discouraged about the future of the church. John Bowen's conviction is that the solution is to be found not in new programs or strategies but in a recovery of theological vision--that of Jesus and his gospel, which transforms every aspect of life. This vision restores hope in the only way realistically possible. Words like mission, discipleship, church, evangelism, renewal, and church planting are used like billiard balls--all rolling around a single table, unconnected and bouncing randomly off one another. This book pulls these ideas together into a coherent and organic whole. The gospel is the hermeneutical key for understanding each of these topics and what draws them together.Thus, chapter 1 is an exposition of the gospel (God's determination to make all things new through Jesus Christ). Chapter 2 discusses discipleship (we only understand discipleship in light of the gospel), and chapter 3 covers church (we only understand church if we understand discipleship). Chapter 4 considers culture as the arena in which the gospel is lived and talked about, and chapter 5 builds on that with a discussion of translation, not only as a missional necessity but as a ministry which itself incarnates the nature of the gospel. The remaining chapters (on evangelism, the future of'inherited churches,'church planting, and leadership) demonstrate how the gospel is the integration point for all. The author's hope is that church leaders--evangelical and mainline, young and old, emerging and traditional, present and future--will have a transformative'Aha!'moment as this gospel hypothesis unfolds."--Publisher.